Implementasi Total Branding dalam Perspektif Semiotika Pemasaran - Angelia Sampurna; Monica Tandian; Viviana Huang; Ruth Florescia Simanjuntak; Rustono Farady Marta (CoverAge: Journal of Strategic Communication, 2020)
The integrated marketing communication process creates positive relationships with consumers, stakeholders, suppliers, and distributors bringing profit through the delivery of carefully planned messages or strategies with integrated marketing objectives. This study aims to describe the implementation of total branding in the application of integrated marketing communication in a food brand, which is seen from many aspects such as brand identity, brand elements, suppliers, distributors, competitors, packaging, and others. The analysis offered by Laura R. Oswald in the semiotic marketing, where the signs, strategies and brand values ​​are interrelated with one another is implemented. The research method is exploratory case studies elaborated with marketing semiotics resting on a constructivism paradigm that thoroughly examines signs and the way they work and can convey meaning to all aspects of marketing activities carried out by Kecap Bango. The results of this study are Kecap Bango’s plan and carry out a through total branding that is in line with the target of the intended marketing.